The Palgrave Handbook of Leisure Theory - Spracklen, Karl; Lashua, Brett; Sharpe, Erin; Swain, Spencer (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This is the first handbook devoted entirely to leisure theory, charting the history and philosophy of leisure, theories in religion and culture, and rational theories of leisure in the Western philosophical tradition, as well as a range of socio-cultural theories from thinkers such as Adorno, Bauman, Weber and Marx. Drawing on contributions from experts in leisure studies from around the world, the four sections cover: traditional theories of leisure; rational theories of leisure; structural theories of leisure; and post-structural theories of leisure. The Palgrave Handbook of Leisure Theory is essential reading for students and scholars working in leisure studies, social theory as well as those working on the problem of leisure in the wider humanities and social sciences.